Insoluble and Thermostable Polyhydroxyesters From a Renewable Natural Occurring Polyhydroxylated Fatty Acid - Benítez, José Jesús; Guzman-Puyol, Susana; Cruz-Carrillo, Miguel Antonio; Ceseracciu, Luca; González Moreno, Ana; Heredia, Antonio; Heredia-Guerrero, José Alejandro (Frontiers in Chemistry, 2019)
To explore the potential of long chain polyhydroxyalkanoates as non-toxic food packaging materials, the characterization of polyesters prepared from a natural occurring polyhydroxylated C16 carboxylic acid (9,10,16-trihydroxyhexadecanoic or aleuritic acid) has been addressed. Such monomer has been selected to elucidate the reactivity of primary and secondary hydroxyl groups and their contribution to the structure and properties of the polyester. Resulting polyaleuritate films have been produced using an open mold in one-step, solvent-free self-polycondensation in melt state. The reaction was carried out directly in air to evaluate the effect of oxygen in the final physical and chemical properties. These polymers are amorphous, insoluble, and thermostable, being therefore suitable for solvent and heat resistant barrier materials. Structurally, most of primary hydroxyls are involved in ester bonds, but there is some branching arising from the partial participation of secondary O-H groups. The oxidative cleavage of the vicinal diol moiety and a subsequent secondary esterification had a noticeable effect on the amorphization and stiffening of the polyester by branching and densification of the ester bond network. A derivation of such structural modification was the surface compaction and the reduction of permeability to water molecules. The addition of Ti(OiPr)4 as a catalyst had a moderate effect, likely because of a poor diffusion within the melt, but noticeably accelerated both the secondary esterification and the oxidative processes. Primary esterification was a high conversion bulk reaction while oxidation and secondary esterification was restricted to nearby regions of the air exposed side of cast films. The reason was a progressive hindering of oxygen diffusion as the reaction progresses and a self-regulation of the altered layer growth. Despite such a reduced extent, the oxidized layer noticeably increased the UV-vis light blockage capacity. In general, characterized physical properties suggest a high potential of these polyaleuritate polyesters as food preserving materials.